The Emerging Role of CD244 Signaling in Immune Cells of the Tumor Microenvironment - Agresta, Laura; Hoebe, Kasper H. N.; Janssen, Edith M. (Frontiers in Immunology, 2018)
In cancer, immune exhaustion contributes to the immunosuppressive tumor microenvironment. Exhausted immune cells demonstrate poor effector function and sustained expression of certain immunomodulatory receptors, which can be therapeutically targeted. CD244 is a Signaling Lymphocyte Activation Molecule (SLAM) family immunoregulatory receptor found on many immune cell types – including NK cells, a subset of T cells, DCs, and MDSCs – that represents a potential therapeutic target. Here, we discuss the role of CD244 in tumor-mediated immune cell regulation.